Association Between Neuroticism and Risk of Lung Cancer: Results From Observational and Mendelian Randomization Analyses - Wei, Xiaoxia; Jiang, Xiangxiang; Zhang, Xu; Fan, Xikang; Ji, Mengmeng; Huang, Yanqian; Xu, Jing; Yin, Rong; Wang, Yuzhuo; Zhu, Meng; Du, Lingbin; Dai, Juncheng; et al. (Frontiers in Oncology, 2022)
Background: It remains undetermined whether neuroticism affects the risk of lung cancer. Therefore, we performed complementary observational and Mendelian randomization (MR) analyses to investigate the association between neuroticism and lung cancer risk. Methods: We included 364,451 UK Biobank participants free of cancer at baseline. Neuroticism was ascertained using the 12-item of Eysenck Personality Inventory Neuroticism Scale. Multivariable Cox regression models were used to calculate hazard ratios (HRs) and 95% confidence intervals (CIs). Two-sample MR analysis was carried out with summary genetic data from UK Biobank (374,323 individuals) and International Lung Cancer Consortium (29,266 lung cancer cases and 56,450 controls). Furthermore, we calculated a polygenic risk score of lung cancer, and examined the joint-effect and interaction between neuroticism and genetic susceptibility on lung cancer risk. Results: During a median follow-up of 7.13 years, 1573 lung cancer cases were documented. After adjusting for smoking and other confounders, higher neuroticism was associated with an increased risk of lung cancer (HR per 1 SD=1.07, 95% CI: 1.02-1.12). Consistently, MR analysis suggested a causal effect of neuroticism on lung cancer risk (OR IVW=1.10, 95% CI: 1.03-1.17). Compared to individuals with low neuroticism and low PRS, those with both high neuroticism and high PRS had the greatest risk of lung cancer (HR=1.82, 95%CI: 1.51-2.20). Furthermore, there was a positive additive but no multiplicative interaction between neuroticism and genetic risk. Conclusions: Our findings suggest that neuroticism is associated with an elevated risk of incident lung cancer, which is strengthened by the genetic susceptibility to lung cancer. Further studies are necessary to elucidate underlying mechanisms.